"I need it now!" Developing a formulaic frame phrasebank for a specific writing assessment: Student perceptions and recommendations. Issue 31 (January 2018) - Hammond, Kay
Abstract: A plethora of research has demonstrated the use of formulaic language in teaching English for academic purposes to participate in discipline-specific communities. However, time-pressured, first-year undergraduates seeking support for writing may prefer a targeted writing resource for their current assignment. In this paper, I detailed the successful development of an assignment-specific academic phrasebank, which provides examples of open-slot, formulaic frames grouped according to the process required to complete an Individual Development Narrative (IDN) essay. Over two cycles of action research ( n 1 = 285, n 2 = 213), first-year health science students offered their perceptions of the Cycle 1 phrasebank and recommendations for improvement primarily relating to promotion, content, and layout. Considering these three factors led to the development of a self-accessed resource in cycle 2 that received a more positive evaluation and uptake from students. These findings may assist future course design and facilitate increased student uptake of support for development of academic writing, especially in large classes. Highlights: The study developed an assignment-specific, formulaic frame phrasebank over two years of action research. Student feedback on the resource showed positive uptake and useful suggestions for development. Student feedback indicated a preference for assignment-specific phrasebanks over general academic phrasebanks. Content, layout and promotion are important factors to consider when designing an assignment-specific phrasebank. The insights will assist other educators to develop self-access phrasebanks for students in large classes.